Changes in nasal septum morphology after rapid maxillary expansion: a Cone-Beam Computed Tomography study in pre-pubertal patient - Giovanni Bruno; Alberto De Stefani; Celeste Benetazzo; Francesco Cavallin; Antonio Gracco (Dental Press Editora, 2020)
ABSTRACT Introduction: Nasal septum deviation (NSD) is the most common structural cause of nasal obstruction, affecting around 65-80% of the adult population. Rapid maxillary expansion (RME) is currently used for treatment of maxillary transverse deficiency, but can also influence nasal cavity geometry. Objective: The present study aimed at evaluating the changes in NSD by using Cone-Beam Computed Tomography (CBCT) scans in pre-pubertal patients treated with RME. Methods: This retrospective exploratory study evaluated 20 pre-pubertal patients (mean age 10 ± 2 years) who were treated for transverse maxillary constriction with RME and presented mild/moderate NSD as an incidental finding. The outcome measures were NSD tortuosity and area. These measures were obtained from transverse and coronal views of records taken before and after RME treatment. Intra-rater reliability was also assessed with intraclass correlation coefficient. Results: NSD was mild in thirteen patients (65%) and moderate in seven (35%). NSD tortuosity index did not significantly change over time (mean difference 0.002 mm/year, 95% CI; p = 0.58). NSD area did not significantly change over time (mean difference 2.103 mm2/year, 95% CI; p = 0.38). Intraclass correlation coefficient was 0.73 (95% CI) for NSD tortuosity and 0.84 (95% CI) for NSD area. Conclusions: NSD tortuosity and area suggested potential changes in NSD with small clinical relevance in pre-pubertal patients who were treated with RME. Additional studies using CBCT scans in larger samples are required to clarify the role of RME in NSD treatment.